The art of living, retro-gradient jives : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Tapsell-Kururangi, James (Massey University, 2018)
Is there an art to living? To make meaning of the sober experience, the shortcomings of my present life. These works, albeit tell of the grief, love, longing, loss, dreams, of living. I try to resist the retrogressive forces of our contemporary cultural, social and political maelstrom. Explored through a series of performative and durational lived works; 1442 Hinemoa St 2017, my childhood home is now an Airbnb, an observation of the domestic home and the surround neoliberal forces in Aōtearoa. Poroporo Road 2017, a journey taken with my uncle to find my grandfather's tin of buried marbles, ontologically observing the Māori ritual of tikanga. An Intercity Bus Ride 2017, a queer passage of grief. FUN-RAZAR 2017, a convivial fundraiser with a latent nomadism, negotiating dematerialising art practice. Two afternoons spent in Mexico City 2017, participation in the tourism economy of Mexico City. Suncake, 2018 a ritualised sharing of cultural ecosystems. A Love Song 2018, a musical cathartic embodiment of grief. Tropical Lab 2018, a study of my mother’s oral histories and geopolitics of international socially engaged residencies. Nans home, an epistemological study of living. I document my humbling experience of what it has been like to frame life as art.
Keywords: Photography; Documentary photography; Zines; New Zealand; Emotions in art; Grief in art; Tango whakaahua; Aronganui; Pōuri; Whanaungatanga; Tūrangawaewae